Analisis Aplikasi Coating Pada Roller Track Cargo Compartment Pada Airbus 330-200/300 - Vetho Tigelrito; Freddy Franciscus; Bismil Rabeta (FTK UNSURYA, 2022)
Aircaft are the most popular means of transportation in the delivery of goods from one area to another. These things can be inaminate objects or living things. Goods transported to the cargo area can be a trigger for damage to the cargo area of the Airbus 330 aircraft, such as spilling fluid from the cargo packaging and the loading process or unloading cargo can cause corrosion in the cargo areaRoller track cargo compartment is one part of the aircraft that is susceptible to corrosion. In aircraft maintenance manual there is no step to apply coating application, where it is known that the coating is one of the protective coatings of a metal to overcome the attack from corrosion. The trial of coating application on the A330-200-200/300 roller track compartment roller track model was conducted for 1670 hours to determine the comparison of roller track corrosion rate values given the av15 adrox protective coating with roller tracks that were not given the av15 adrox protective coating. The test results obtained that the average value of corrosion rate of roller track models with coating coating layers is 0.1505 and without coating layer which is 0.4045 mmpy with coating usage efficiency of 62.7%. So it can be concluded that the application of coating on roller track cargo compartment is effective in inhibiting corrosion rate.